Genetics of disease resistance in small ruminants in Africa - Baker, R.L. (1995)
Disease is one of the most important biological constraints to small ruminant production in the many different agroclimatic zones of Africa. Loss of production, high levels of mortality and the cost of drugs are some of the major concerns. Current control strategies include vaccination, medication, isolation of animals from pathogens and improved sanitation for management systems. In Africa, many control strategies are limited by lack of efficient veterinary services, unavailability or high costs of drugs and vaccines, increasing occurrence of drug resistance by pathogens and limited scope to improve management cost-effectively. an attractive solution is to breed for disease resistance. There is a large and diverse range of indigenous breeds of sheep and goats in Africa, some of which appear to be genetically resistant or tolerant to disease. The limited ata on between- and within-breed genetic variation in resistance to helminthiasis and trypanosomiasis are reviewed and the need for further characterisation is identified. Evidence for the genetic basis of disease resistance in sheep in countries outside Africa, suggests that breeding for diseases resistance could be a viable control method. More information on genetic parameters of disease resistance and better assessment of the economic impact of disease is required to develop appropriate breeding strategies.